INTERETHNIC RELATIONSHIP AND SOCIAL HARMONY: SOCIAL INTERACTION BETWEEN MADURESE AND OTHER ETHNICS IN SUMENEP REGENCY - Badriyanto, Bambang Samsu (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
Indonesia is a multiethnic nation that has various physical characteristic and culture. Each ethnic has its own characteristic, the skin color, langguage, art, custom, social structurem and cultureThese variousity of human and culture is a form of human adaptation process into the different environment as the result of the wide archipelago area. In the process of a country development, since the independence era until today, it seems that one particular ethnic has a different development level to the other. In fact, today there is a high tendency of discrepancy among ethnics, whether it is the aspect of economy, social, technology, politic, or culture. This discrepency has an implicatioin of horizontal conflict trigerred by the jelousy regarding the matter of economy, social, culture. The ethnic of madura is one of some ethnics in Indonesia with a high rate of migration. They live in several area of Indonesia, particularly Java, Sumatera, and Kalimantan. Due to the natural resources limitation in madura, about 70 % Madurese live and reside the Madura island (Djojomartono, 1985). They work in various sector, particularly the informal sectors, services, and fisherman. This article is based on research focused onÂ interethnic relationship and social harmony: social interaction between Madurese and other ethnics in Sumenep regency.Â